The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/2319714520968705
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Influence of Private Labels on Sales of National Brands: A Qualitative Approach

Abstract: Private-label brands (PLBs) are spreading their operations in all product categories and have marked their presence in almost all types of retail formats. They are posing stringent competition to national brands (NBs), be it offline (organized and unorganized) retail or online retail. Besides being favourites of value-conscious Indian consumers, PLBs are becoming a key focus of channel partners as well. In this context, the present research article is aimed at providing insights about how PLBs are able to garn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
(116 reference statements)
0
6
0
Order By: Relevance
“…Research on respondent behaviour is often conducted by collecting qualitative data in the form of responses or reactions recorded in the form of written transcripts (Castleberry and Nolen, 2018). Additionally, focus group interviews and observation methods are employed to produce content for the research purpose (Baker, 2006; Islam et al ., 2021). Qualitative research provides deeper insights into respondents' perceptions and experiences about the phenomena under study (Rosenthal, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Research on respondent behaviour is often conducted by collecting qualitative data in the form of responses or reactions recorded in the form of written transcripts (Castleberry and Nolen, 2018). Additionally, focus group interviews and observation methods are employed to produce content for the research purpose (Baker, 2006; Islam et al ., 2021). Qualitative research provides deeper insights into respondents' perceptions and experiences about the phenomena under study (Rosenthal, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, enhancing the assortment of eco-friendly products in retail setup and utilizing retailers' referral power can facilitate cultivating green purchase intention in consumers [32,48]. Furthermore, retail stores with the help of marketing artifacts provide valuable communication of green consumption to consumers which enables generating positive intention toward performing green consumption [49].…”
Section: Preference For Retail Storementioning
confidence: 99%
“…We found that it was important to manage their expectations and maintain the level of trust. Different stressors and their remedies (Amin & Khan, 2021), alternatives (Parihar et al, 2021) and strategic innovations (Bhalla, 2021;Islam et al, 2021;Zaoui et al, 2021) added to the possibilities for questioning and answering multiple contexts.…”
Section: Sudhir Ranamentioning
confidence: 99%